INFLUENCE OF DIGITAL MARKETING BRAND IMAGE AND SERVICE QUALITY ON CONSUMER PURCHASE INTEREST OF MS GLOW (Case Study Of Fe University Islamic Lamongan) - Eka Washilatus Suryani; M. Rizal Nur Irawan; Nurus Safa’atillah (Sean Institute, 2023)
The purpose of this study was to determine partially and simultaneously as well as the most dominant variables the Influence Of Digital Marketing Brand Image And Service Quality On Consumer Purchase Interest in MS Glow at FE Lamongan Islamic University. This study has a population and a sample of 75 respondents. Analysis of the data used is multiple linear regression analysis. That partially Digital Marketing (X 1 ), Brand Image (X 2 ) and Service Quality (X 3 ) variables have a significant influence on Purchase Interest (Y) of MS Glow products at the Faculty of Economics, Lamongan Islamic University. The most dominant variable from this research is Brand Image (X 2 ) by looking at the regression coefficient value in multiple linear regression analysis